Health Facility-Based Maternal Mortality in Nigeria: A Systematic Review and Meta-analysis - Haruna, Iman; Yakasai, Ahmad; Haruna, Sadiya; Yau, Jamila; Jaafar, Yusuf; Muhammad, Hamza; Tukur, Jamilu (Nigerian Journal of Basic and Clinical Sciences, 2026)
Nigeria has been reaffirming its commitment to reducing maternal death at national and international levels. Multiple strategies have therefore been formulated at different levels of the maternal healthcare delivery chain including health facilities. However, varying rates of maternal death are still being reported from health facilities in Nigeria. This study aimed at exploring the trend in maternal death across health facilities in Nigeria to guide policy making and/ or implementation. A systematic review and meta-analysis of studies conducted in Nigeria was undertaken according to standard protocol. Random and fixed effects model procedures were used to pool estimates from the studies that satisfied the inclusion criteria. Derived estimates were examined for heterogeneity, publication bias and quality using I-squared statistic, Egger’s/Begg’s tests and modified Downs/Black checklist respectively. The pooled maternal mortality ratio for Nigeria derived from 24 studies that reported data for 96 health facilities was 1470 per 100,000 live births. In restricted analysis, estimates for geopolitical zones were: South East (SE) 1449; South South (SS) 1825; South West (SW) 1564; North Central (NC) 1769; North East (NE) 1670 and North West 1530(NW). There was no publication bias in all analyses even though small sample size in restricted analysis and differing study duration may influence pooled estimates. Health facility-derived maternal mortality in Nigeria is unprecedentedly high and appropriate measures need to be put in place to reduce the MMR in Nigeria and Sub-Saharan Africa as a whole.